Environmentally friendly asphalt material and preparation method thereof

Through the combination of silicon oxygen structure wrapped with ceramic granules and minerals, the problem of aging of asphalt materials is solved, the durability and stability of asphalt are improved, and the antibacterial and antibacterial properties are enhanced, and the recycling and utilization of industrial waste and exhaust degradation are realized.

CN117865556BActive Publication Date: 2024-12-17HUZHOU TRAFFIC GREEN ENVIRONMENTAL PROTECTION NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311662012.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-06
Publication Date
2024-12-17
Estimated Expiration
2043-12-06

AI Technical Summary

Technical Problem

The existing asphalt materials age during use, resulting in reduced adhesion, reduced road hardening, cracks and durability, and difficulty in repairing.

Method used

The method of wrapping ceramic particles with silicon oxygen structure is adopted to improve the durability and stability of asphalt materials by modifying the combination of porous ceramic particles and minerals, forming a thermal conductivity network, enhancing chemical links and antibacterial and antibacterial properties, and using red mud to improve the Pavement purification performance.

Benefits of technology

It effectively solves the problem of asphalt aging, improves the durability and stability of asphalt materials, enhances the antibacterial and antibacterial properties, and realizes the recycling and utilization of industrial waste and exhaust degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004590516280000181
    Figure BDA0004590516280000181
Patent Text Reader

Abstract

The present invention belongs to the technical field of asphalt materials, and specifically relates to an environmentally friendly asphalt material and a preparation method thereof, wherein the mass ratio of the environmentally friendly asphalt material includes: 20-40 parts of ceramsite, 15-20 parts of mineral material, 3-10 parts of asphalt, 20-30 parts of red mud, and 0.5-1 parts of surfactant, and provides a specific preparation method. The present invention solves the aging problem of existing asphalt, and uses a silicon-oxygen structure to wrap ceramsite to achieve excellent and stable connectivity of ceramsite, thereby improving the durability and stability of asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of asphalt materials, and in particular relates to an environmentally friendly asphalt material and a preparation method thereof. Background Art

[0002] Asphalt is the main pavement material in domestic and foreign road projects, and is also the main raw material for waterproofing materials. Colored asphalt has been widely used in the construction of landscape roads, bicycle paths, sidewalks, and walking paths in tourist attractions because it can improve the recognizability of the road surface. During use, due to heating and various natural factors, asphalt gradually ages and the colloidal structure changes, resulting in a decrease in asphalt penetration, an increase in viscosity, and a decrease in ductility. The aging of asphalt weakens the bonding force between asphalt and aggregate particles, causing the hardening of asphalt concrete pavement, which in turn causes the pavement particles to fall off and become loose, reducing the durability of the road. The most intuitive phenomenon is the appearance of cracks on the pavement, which is difficult to repair. Summary of the invention

[0003] In response to the problems in the prior art, the present invention provides an environmentally friendly asphalt material, which solves the aging problem of the existing asphalt. The expanded clay is wrapped with a silicon-oxygen structure to achieve excellent and stable connectivity of the expanded clay, thereby improving the durability and stability of the asphalt.

[0004] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0005] An environmentally friendly asphalt material, the mass ratio of which includes:

[0006] 20-40 parts of ceramsite, 15-20 parts of mineral material, 3-10 parts of asphalt, 20-30 parts of red mud, and 0.5-1 part of surfactant.

[0007] The ceramsite is modified porous ceramsite, which has the multifunctional characteristics of light weight, corrosion resistance, frost resistance, earthquake resistance and good insulation. Adding ceramsite as a filling material to asphalt can effectively reduce costs. At the same time, the surface of ceramsite is smooth and hard, and the interior is honeycomb-shaped. It has the characteristics of low density, low thermal conductivity and high strength, which effectively reduces the lightweight of asphalt materials. However, the surface of ceramic particles has a certain inertia, resulting in weak surface adhesion and poor connection stability with other materials. To solve this problem, the porous ceramsite is silica-oxygen porous ceramsite, and the preparation method of the silica-oxygen porous ceramsite includes the following steps: a1, ethyl cellulose is added to ether and stirred evenly to form a dissolved solution, and then trichlorophenylsilane is added and stirred rapidly for 20-30 minutes to obtain a homogeneous dissolved solution. The ethyl cellulose is in ether. The concentration of trichlorophenylsilane is 100-200g / L, the stirring speed is 100-200r / min, the amount of trichlorophenylsilane added is 150-200% of the mass of ethyl cellulose, and the stirring speed of rapid stirring is 500-1000r / min. This step utilizes the solubility of ethyl cellulose and trichlorophenylsilane in ether to form a homogenized dispersion, and at the same time utilizes the mutual solubility of the liquid phase to form a good mutual solubility effect between ethyl cellulose and trichlorophenylsilane; a2, adding fly ash, bentonite, sludge and kaolin into a grinder for grinding to obtain a mixed powder, wherein the mass ratio of fly ash, bentonite, sludge and kaolin is 30-40:5-10:5-15: 1. The grinding pressure of the grinding treatment is 2-3MPa. In this step, the solid materials are evenly mixed and dry-grinded to achieve simultaneous particle refinement and mixing, thereby achieving the effect of component mixing; a3. The mixed powder is added to the dissolved solution for ultrasonic dispersion for 2-4 hours to obtain a mixed slurry. The concentration of the mixed powder in the dissolved solution is 1000-4000g / L. The ultrasonic frequency of the ultrasonic treatment is 60-80kHz and the temperature is 5-10°C. In this step, the mixed powder is added to the dissolved solution to form a suspension system, and the suspension system is dispersed by ultrasonic treatment to ensure that the surface bubbles of the mixed powder are removed to achieve excellent homogeneous dispersion; secondly, during the ultrasonic process, the mixed powder The surface cracks of the material are pulverized in ultrasound, and the particles are further crushed; a4, after filtering the mixed slurry, put it into a reactor and let it stand for 2-4 hours, then stir the reactor and purge it for 1-2 hours to obtain a mixed material, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, the standing temperature is 5-10°C, the stirring speed of the stirred reactor is 500-800r / min, and the purge uses nitrogen at 35-40°C, and the purge speed is 5-10mL / min; this step removes excess liquid in the slurry by filtering, while ensuring that trichlorophenylsilane and ethyl cellulose form a good liquid film on the surface of the mixed powder;The mixed powder with the liquid film is placed in a reactor and allowed to stand, and the water vapor in the reactor and the slightly soluble system of ether can be used to form an in-situ hydrolysis reaction of trichlorophenylsilane, and the reaction is carried out on the particle surface of the mixed powder; a5, the mixed material is granulated to form solid particles, and sintered at a constant temperature for 1-2 hours, and then placed in a muffle furnace for sintering for 20-30 minutes, and then washed and allowed to stand and dry to obtain ceramsite; the constant temperature sintering temperature is 150-180°C; the sintering temperature of the muffle furnace is 1000-1100°C; this step The mixed material is granulated to form granules. The granulated powder forms a bonding system through ethyl cellulose and silane hydrolyzate. During constant temperature sintering, the silane hydrolyzate forms a condensation structure to achieve a polymerization effect. At the same time, ethyl cellulose acts as a barrier in the temperature system to form a barrier position in the granule, and is converted into a decomposition product in the subsequent sintering process and directly discharged. At the same time, the silane hydrolyzate forms a condensation to form a mesoporous structure support system in the granule. At the same time, the mesoporous structure effectively improves the permeability of the porous ceramsite. The porous ceramsite is functionalized by modification, which effectively improves the viscosity and internal antibacterial property of the ceramsite. The modifier of the porous ceramsite is ethyl silicate and n-butyl titanate. The preparation method of the modified porous ceramsite comprises the following steps: b1, placing the porous ceramsite in distilled water for ultrasonication for 20-50 minutes, and drying at a constant temperature to obtain clean porous ceramsite. The mass ratio of the porous ceramsite to distilled water is 1:5-10, the ultrasonic frequency of the ultrasonication is 50-80kHz, and the temperature is 30-50°C; the temperature of the constant temperature drying is 110-120°C; this step utilizes the washing ability of distilled water and the high-frequency vibration of the ultrasonication to promote the distilled water to enter the particle system of the porous ceramsite, thereby achieving a good cleaning effect, and at the same time, the water molecules are taken out during the constant temperature drying to achieve a drying effect; b2, adding titanium tetrachloride to ethanol to form a dissolving solution, spraying The reaction kettle is sprayed with mist to form a steam atmosphere, and clean porous ceramics are placed in it. After standing for 20-30 minutes, the temperature is lowered to 90-100°C to obtain coated porous ceramsite. The concentration of titanium tetrachloride in ethanol is 80-100g / L, the spray temperature is 140-150°C, the porous ceramics are placed in the middle section of the reaction kettle, and the standing temperature is 140-150°C. This step utilizes the good solubility of titanium tetrachloride in ethanol to form a stable solution, and the solution is used as the atmosphere to form a steam atmosphere in the reaction kettle. When the porous ceramics are then placed in it, the inside and outside of the porous ceramics are neatly infiltrated. After complete infiltration, the titanium tetrachloride is converted into a liquid by cooling, and adheres to the specific surface area of ​​the porous ceramics according to its own viscosity, thereby achieving good coating properties, while the ethanol remains neat, and an excellent separation effect can be achieved.b3, allowing the coated porous ceramsite to stand in a reactor for 1-2 hours to obtain a preliminarily hydrolyzed porous ceramic, wherein the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, and the standing temperature is 5-10°C. This step utilizes the permeability of water vapor during the standing process to penetrate into the surface of the coated porous ceramsite, and hydrolyzes titanium tetrachloride into tetrahydroxytitanic acid; b4, adding ethyl silicate to ether and stirring evenly to form a silicon ether liquid, and then spraying the silicon ether liquid onto the surface of the preliminarily hydrolyzed porous ceramic, and standing at a constant temperature to obtain a surface-coated porous ceramic; the concentration of ethyl silicate in ether is 50-70g / L, the stirring speed is 400-600r / min, and the spraying speed is 0.1-0.3mL / cm; 2 , the temperature of the constant temperature standing is 40-50°C, and this step uses a spray method to deposit the silicon ether liquid to initially hydrolyze the surface of the porous ceramic to achieve external surface deposition, and the ether is removed during the constant temperature standing to form a liquid film. The coating forms a liquid film on the external surface by spraying, and basically will not be formed in the gap; b5, the surface-coated porous ceramsite is allowed to stand in a reactor for 20-30 minutes, and modified porous ceramsite is obtained after sintering. The atmosphere in the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10-12:1, and the standing temperature is 30-40°C; the temperature of the sintering treatment is 120-150°C; this step uses water vapor to hydrolyze ethyl silicate to form a silicic acid structure, and cooperates with the titanic acid layer on the surface to form a stable silicon-titanium oxidation condensation structure during the sintering process, thereby achieving the effect of surface modification. In the modified ceramsite, titanium tetrachloride is fixed on the specific surface of the porous ceramsite through the vapor deposition and in-situ hydrolysis system of steam, and ethyl silicate is deposited on the outer surface by surface spraying, and in the subsequent sintering process, a titanium dioxide film layer is formed on the inner surface, and a titanium dioxide film and a silicon dioxide film are formed on the outer surface from the inside to the outside, and a stable connection is formed between the two through the oxidation system in the polycondensation process; the modified porous ceramsite prepared by this process has an internal and external double modified structure, that is, the internal titanium dioxide is modified, and the external titanium dioxide-based silicon dioxide is modified. After the ethyl silicate is hydrolyzed, silicon dioxide is formed, which has good light transmittance, and it will directly irradiate the titanium dioxide surface during the illumination process. At the same time, based on the titanium dioxide film uniformly wrapped on the specific surface of the porous ceramsite, it belongs to an integrated structure, and the titanium dioxide in the porous ceramsite is active and can show good antibacterial and antimicrobial properties.

[0008] The mineral material is composed of coarse aggregate, fine aggregate and mineral powder, and the mass ratio of coarse aggregate, fine aggregate and mineral powder is 4-5:3:1-2. The coarse aggregate is 8-10mm basalt, and the fine aggregate is limestone less than 2.5mm. The mineral material is a commonly used asphalt filler. Mineral materials of different particle sizes are mixed with asphalt to produce asphalt mortars of different systems. The asphalt mortar shows different mortar permeability in the whole system, can penetrate into the whole system, play an excellent permeability, and improve the internal binding effect of the asphalt material. The mineral material is pre-treated before use, and the pre-treatment steps include: b1, putting the coarse aggregate and the fine aggregate into ethanol for ultrasonic treatment for 10-20min, After filtering, drying is performed to obtain a preliminary mixed aggregate. The raw material concentration of the ultrasonic treatment is 100-200 g / L, the ultrasonic frequency is 60-80 kHz, the temperature is 20-40°C, and the drying temperature is 80-100°C. This step uses ethanol ultrasound to mix the coarse aggregate and the fine aggregate, and removes the floating dust on the coarse aggregate and the fine aggregate, thereby improving the surface cleanliness of the coarse aggregate and the fine aggregate. b2, ethyl silicate is added to ether and stirred evenly to form a dissolved solution, and then the preliminary mixed aggregate is placed and ultrasonically treated for 30-50 minutes; a suspended slurry is obtained, the concentration of ethyl silicate in ether is 100-200 g / L, and the stirring speed for stirring evenly is 300 -500r / min, the concentration of the preliminary mixed aggregate in the dissolving solution is 200-500g / L, the frequency of the ultrasonic treatment is 50-80kHz, and the temperature is 10-15°C; this step utilizes the solubility of ethyl silicate in ether to form good solubility. At the same time, when the preliminary mixed aggregate is put in, the ultrasonic treatment can homogeneously disperse the ethyl silicate on the surface of fine aggregate and coarse aggregate to form a surface liquid film, thereby loading the ethyl silicate on the surface of the preliminary mixed aggregate; b3, add the mineral powder to the suspension and ultrasonically disperse it for 20-30min, then dry it, and blow it into the reactor at a constant temperature to obtain the pre-treated mineral material after deposition. The temperature of the ultrasonic dispersion is 10-20°C, and the ultrasonic The frequency is 60-90kHz, the drying temperature is 40-60℃; the constant temperature blowing temperature is 70-80℃, the blowing speed is 3-6g / min, the atmosphere of the reactor is a mixed atmosphere of water vapor and nitrogen in a volume ratio of 1:9, and the deposition temperature is 100-140℃; this step uses blowing to allow the mineral material to enter the reactor, and the distilled water in the reactor can react with the ethyl silicate on the surface of the mineral material. This reaction is an in-situ hydrolysis reaction, and the in-situ hydrolyzate still remains on the surface of the mineral material, and gradually forms a silicon-oxygen structure at the subsequent deposition temperature. Therefore, the silicon-oxygen structure on the mineral material forms a surface wrapping, and a light-transmitting film is formed on the surface of the mineral material.The mineral material prepared by this method has encapsulation characteristics, forming excellent silicon-oxygen activity, improving its connection ability with asphalt, and also promoting the activity of asphalt mortar. At the same time, the silicon-oxygen structure on the surface of the mineral material has light transmission and reflectivity, which can promote the transmission of light in the entire asphalt material, thereby increasing the light contact area of ​​titanium dioxide in the expanded clay, thereby improving the overall antibacterial and bactericidal properties.

[0009] The asphalt is one or both of national standard No. 70 asphalt and No. 90 asphalt. The asphalt has moderate hardness and consistency, strong shear damage resistance, and is easy to apply in construction.

[0010] The surfactant is dodecyl trimethyl ammonium chloride, which not only has stable chemical properties, but also has heat resistance, light resistance, antistatic and antibacterial properties.

[0011] Red mud is a material that uses red mud with rich pore structure and high specific surface area to modify asphalt, which can make porous asphalt materials have excellent adsorption effect on road pollutants; at the same time, the high specific surface area of ​​red mud can make the pores of porous asphalt pavement materials finer, so that the distance between particles is closer, the friction effect is enhanced, and the mechanical properties, anti-scattering performance and stability of porous asphalt pavement materials are effectively improved; in addition, red mud is rich in elements such as iron, aluminum, sodium and potassium. The alkaline substances formed under the action of rainwater can effectively precipitate runoff pollutants, among which Fe 3+ and Al 3+ Can be used with PO4 3- Complex precipitation, Na + and K + Able to interact with NH4 + Exchange can effectively reduce the pollution of phosphorus and nitrogen in runoff pollutants; in addition, the present invention can synergize with red mud by adding expanded clay and mineral materials, produce a bridging filter effect on the sediment, adsorb and retain more pollutants, and further improve the purification performance of the porous asphalt material; at the same time, expanded clay and mineral materials can be used as skeleton materials to effectively improve the splitting strength of the porous asphalt material, and further improve the mechanical properties of the porous asphalt material.

[0012] The method for preparing the environmentally friendly asphalt material comprises the following steps:

[0013] Step 1, stirring ceramsite, mineral material and red mud at high speed to form a mixture; the speed of high-speed stirring is 500-700r / min;

[0014] Step 2, stirring and heating the asphalt to 160-180° C. at a stirring speed of 200-400 r / min to obtain preheated asphalt;

[0015] Step 3, adding a surfactant to the mixture and stirring, and then adding preheated asphalt to obtain an environmentally friendly asphalt material, wherein the stirring speed is 300-500 r / min.

[0016] It can be seen from the above description that the present invention has the following advantages:

[0017] 1. The present invention solves the aging problem of existing asphalt, and utilizes the method of wrapping ceramsite with a silicon-oxygen structure to achieve excellent and stable connectivity of ceramsite, thereby improving the durability and stability of asphalt.

[0018] 2. The present invention adopts a modified method to form a heat-conducting network on the surface of expanded clay, thereby eliminating the heat island problem caused by the poor thermal conductivity of expanded clay and alleviating the thermal aging problem inside the asphalt. At the same time, the titanium-oxygen system and the silicon-oxygen system have good chemical activity and can achieve excellent chemical link stability.

[0019] 3. The present invention utilizes a silicon-oxygen system as a coating layer to coat the mineral material and expanded clay, and to light-excite the titanium dioxide to form a certain antibacterial and antimicrobial effect; combined with the antibacterial property of the surfactant itself, it has multiple antibacterial and antimicrobial properties.

[0020] 4. The present invention uses red mud, expanded clay and mineral materials as raw materials, realizes the recycling of industrial waste and greatly reduces environmental pressure. At the same time, the present invention uses silicon oxide material as the packaging structure and the pore structure of the raw materials to degrade automobile exhaust under light and reduce exhaust pollution. DETAILED DESCRIPTION

[0021] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0022] Example 1

[0023] An environmentally friendly asphalt material, the mass ratio of which includes:

[0024] 20 parts of expanded clay, 15 parts of mineral material, 3 parts of asphalt, 20 parts of red mud, and 0.5 parts of surfactant.

[0025] The ceramsite adopts modified porous ceramsite, and the porous ceramsite adopts silica porous ceramsite, and the preparation method of the silica porous ceramsite comprises the following steps: a1, adding ethyl cellulose to ether and stirring evenly to form a dissolving solution, then adding trichlorophenylsilane and rapidly stirring for 20 minutes to obtain a homogeneous dissolving solution, the concentration of the ethyl cellulose in the ether is 100g / L, the stirring speed is 100r / min, the amount of the trichlorophenylsilane added is 150% of the mass of the ethyl cellulose, and the stirring speed of the rapid stirring is 500r / min; a2, adding fly ash, bentonite, sludge and kaolin into a grinder for grinding treatment to obtain a mixed powder, the mass ratio of the fly ash, bentonite, sludge and kaolin is 30:5:5:1, and the grinding pressure of the grinding treatment is 2MPa; a3, adding the mixed powder into Ultrasonic dispersion is performed in the dissolving solution for 2 hours to obtain a mixed slurry, wherein the concentration of the mixed powder in the dissolving solution is 1000 g / L, the ultrasonic frequency of the ultrasonic treatment is 60 kHz, and the temperature is 5°C; a4, after filtering the mixed slurry, it is placed in a reactor and allowed to stand for 2 hours, then the reactor is stirred and purged for 1 hour to obtain a mixture, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, the standing temperature is 5°C, the stirring speed of the stirred reactor is 500 r / min, and purging uses 35°C nitrogen at a purging speed of 5 mL / min; a5, granulating the mixture to form solid particles, and sintering at a constant temperature for 1 hour, then placing it in a muffle furnace and sintering it for 20 minutes, and then standing and drying after cleaning to obtain ceramsite; the constant temperature sintering temperature is 150°C; the sintering temperature of the muffle furnace is 1000°C.

[0026] Furthermore, the preparation method of the modified porous ceramsite includes the following steps: b1, placing the porous ceramsite in distilled water for ultrasonic treatment for 20 minutes, and drying at a constant temperature to obtain clean porous ceramsite, wherein the mass ratio of the porous ceramsite to distilled water is 1:5, the ultrasonic frequency of the ultrasonic treatment is 50kHz, and the temperature is 30°C; the temperature of the constant temperature drying is 110°C; b2, adding titanium tetrachloride to ethanol to form a dissolving solution, spraying it into a reactor to form a steam atmosphere, and placing the clean porous ceramic in it, standing it for 20 minutes, and then cooling it to 90°C to obtain a coated porous ceramsite, wherein the concentration of titanium tetrachloride in ethanol is 80g / L, and the spraying temperature is 140 ℃, the porous ceramic is placed in the middle section of the reactor, and the standing temperature is 140℃; b3, the coated porous ceramsite is allowed to stand in the reactor for 1h to obtain a preliminary hydrolyzed porous ceramic, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, and the standing temperature is 5℃; b4, ethyl silicate is added to ether and stirred evenly to form a silicon ether liquid, and then the silicon ether liquid is sprayed onto the surface of the preliminary hydrolyzed porous ceramic, and the surface is allowed to stand at a constant temperature to obtain a surface coated porous ceramic; the concentration of ethyl silicate in ether is 50g / L, the stirring speed is 400r / min, and the spraying speed is 0.1mL / cm 2 , the constant temperature standing temperature is 40°C; b5, the surface coated porous ceramsite is stood in the reactor for 20 minutes, and the modified porous ceramsite is obtained after sintering treatment. The atmosphere in the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, and the standing temperature is 30°C; the temperature of the sintering treatment is 120°C.

[0027] The mineral material is composed of coarse aggregate, fine aggregate and mineral powder, and the mass ratio of coarse aggregate, fine aggregate and mineral powder is 4:3:1, the coarse aggregate is 8-10mm basalt, and the fine aggregate is limestone less than 2.5mm; the mineral material is pre-treated before use, and the pre-treatment steps include: b1, putting the coarse aggregate and the fine aggregate into ethanol for ultrasonic treatment for 10min, filtering and drying to obtain a preliminary mixed aggregate, the raw material concentration of the ultrasonic treatment is 100g / L, the ultrasonic frequency is 60kHz, the temperature is 20℃, and the drying temperature is 80℃; b2, adding ethyl silicate to ether and stirring evenly to form a dissolved solution, and then putting the preliminary mixed aggregate into and ultrasonically treating it for 30min; obtaining a suspended slurry, the concentration of ethyl silicate in ether is 100g / L, the stirring speed for uniform stirring is 300r / min, the concentration of the preliminary mixed aggregate in the dissolved solution is 200g / L, the frequency of ultrasonic treatment is 50kHz, and the temperature is 10℃;

[0028] b3, adding mineral powder to the suspension and ultrasonically dispersing it for 20 minutes, then drying it, and blowing it into the reactor at a constant temperature to obtain the pre-treated mineral material through deposition, the temperature of the ultrasonic dispersion is 10°C, the ultrasonic frequency is 60kHz, the temperature of the drying is 40°C; the temperature of the constant temperature blowing is 70°C, the blowing rate is 3g / min, the atmosphere of the reactor is a mixed atmosphere of water vapor and nitrogen in a volume ratio of 1:9, and the temperature of the deposition is 100-°C.

[0029] The asphalt adopts national standard No. 70 asphalt.

[0030] The surfactant is dodecyltrimethylammonium chloride.

[0031] The method for preparing the environmentally friendly asphalt material comprises the following steps:

[0032] Step 1, stirring ceramsite, mineral material and red mud at high speed to form a mixture; the speed of high-speed stirring is 500r / min;

[0033] Step 2, stirring and heating the asphalt to 160° C. at a stirring speed of 200 r / min to obtain preheated asphalt;

[0034] Step 3, adding a surfactant to the mixture and stirring, and then adding preheated asphalt to obtain an environmentally friendly asphalt material, the stirring speed is 300r / min.

[0035] Example 2

[0036] An environmentally friendly asphalt material, the mass ratio of which includes:

[0037] 40 parts of expanded clay, 20 parts of mineral material, 10 parts of asphalt, 30 parts of red mud, and 1 part of surfactant.

[0038] The ceramsite adopts modified porous ceramsite, and the porous ceramsite adopts silica porous ceramsite, and the preparation method of the silica porous ceramsite comprises the following steps: a1, adding ethyl cellulose to ether and stirring evenly to form a dissolving solution, then adding trichlorophenylsilane and rapidly stirring for 30 minutes to obtain a homogeneous dissolving solution, the concentration of the ethyl cellulose in the ether is 200g / L, the stirring speed is 200r / min, the amount of the trichlorophenylsilane added is 200% of the mass of the ethyl cellulose, and the stirring speed of the rapid stirring is 1000r / min; a2, adding fly ash, bentonite, sludge and kaolin into a grinder for grinding treatment to obtain a mixed powder, the mass ratio of the fly ash, bentonite, sludge and kaolin is 40:10:15:1, and the grinding pressure of the grinding treatment is 3MPa; a3, adding the mixed powder to Ultrasonic dispersion in the dissolving liquid for 4 hours to obtain a mixed slurry, the concentration of the mixed powder in the dissolving liquid is 4000g / L, the ultrasonic frequency of the ultrasonic treatment is 80kHz, and the temperature is 10°C; a4, after filtering the mixed slurry, put it into a reactor and let it stand for 4 hours, then stir the reactor and purge it for 2 hours to obtain a mixture, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, the standing temperature is 10°C, the stirring speed of the stirred reactor is 800r / min, and purging uses 40°C nitrogen at a purge speed of 10mL / min; a5, granulate the mixture to form solid particles, and sinter at a constant temperature for 2 hours, then put it into a muffle furnace and sinter for 30 minutes, and then stand and dry after cleaning to obtain ceramsite; the constant temperature sintering temperature is 180°C; the sintering temperature of the muffle furnace is 1100°C.

[0039] Furthermore, the preparation method of the modified porous ceramsite includes the following steps: b1, placing the porous ceramsite in distilled water for ultrasonic treatment for 50 minutes, and drying at a constant temperature to obtain clean porous ceramsite, wherein the mass ratio of the porous ceramsite to distilled water is 1:10, the ultrasonic frequency of the ultrasonic treatment is 80kHz, and the temperature is 50°C; the temperature of the constant temperature drying is 120°C; b2, adding titanium tetrachloride to ethanol to form a dissolving solution, spraying it into a reactor to form a steam atmosphere, and placing the clean porous ceramic in it, standing it for 30 minutes, and then cooling it to 100°C to obtain a coated porous ceramsite, wherein the concentration of titanium tetrachloride in ethanol is 100g / L, and the spraying temperature is 15 0℃, the porous ceramic is placed in the middle of the reactor, and the standing temperature is 150℃; b3, the coated porous ceramsite is allowed to stand in the reactor for 2h to obtain a preliminary hydrolyzed porous ceramic, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, and the standing temperature is 10℃; b4, ethyl silicate is added to ether and stirred evenly to form a silicon ether liquid, and then the silicon ether liquid is sprayed onto the surface of the preliminary hydrolyzed porous ceramic, and the surface is allowed to stand at a constant temperature to obtain a surface coated porous ceramic; the concentration of ethyl silicate in ether is 70g / L, the stirring speed is 600r / min, and the spraying speed is 0.3mL / cm 2 , the constant temperature standing temperature is 50°C; b5, the surface coated porous ceramsite is stood in the reactor for 30 minutes, and the modified porous ceramsite is obtained after sintering treatment. The atmosphere in the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 12:1, and the standing temperature is 40°C; the temperature of the sintering treatment is 150°C.

[0040] The ore material is composed of coarse aggregate, fine aggregate and mineral powder, and the mass ratio of the coarse aggregate, fine aggregate and mineral powder is 5:3:2. The coarse aggregate is 8-10 mm basalt, and the fine aggregate is limestone less than 2.5 mm. The ore material is pre-treated before use, and the pre-treatment steps include: b1, putting the coarse aggregate and the fine aggregate into ethanol for ultrasonic treatment for 20 minutes, filtering and drying to obtain a preliminary mixed aggregate, the raw material concentration of the ultrasonic treatment is 200 g / L, and the ultrasonic frequency is b2, adding ethyl silicate to ether and stirring evenly to form a dissolving solution, then putting the preliminary mixed aggregate into the solution and ultrasonically treating it for 50 minutes; obtaining a suspension slurry, wherein the concentration of ethyl silicate in ether is 200 g / L, the stirring speed for uniform stirring is 500 r / min, the concentration of the preliminary mixed aggregate in the dissolving solution is 500 g / L, the frequency of ultrasonic treatment is 80 kHz, and the temperature is 15°C;

[0041] b3, adding mineral powder to the suspension and ultrasonically dispersing it for 30 minutes, then drying it, and blowing it into the reactor at a constant temperature to obtain the pre-treated mineral material through deposition, the temperature of the ultrasonic dispersion is 20°C, the ultrasonic frequency is 90kHz, the temperature of the drying is 60°C; the temperature of the constant temperature blowing is 80°C, the blowing speed is 6g / min, the atmosphere of the reactor is a mixed atmosphere of water vapor and nitrogen in a volume ratio of 1:9, and the temperature of the deposition is 140°C.

[0042] The asphalt is No. 90 asphalt.

[0043] The surfactant is dodecyltrimethylammonium chloride.

[0044] The method for preparing the environmentally friendly asphalt material comprises the following steps:

[0045] Step 1, stirring ceramsite, mineral material and red mud at high speed to form a mixture; the speed of high-speed stirring is 700r / min;

[0046] Step 2, stirring and heating the asphalt to 180° C. at a stirring speed of 400 r / min to obtain preheated asphalt;

[0047] Step 3, adding a surfactant to the mixture and stirring, and then adding preheated asphalt to obtain an environmentally friendly asphalt material, the stirring speed is 500r / min.

[0048] Example 3

[0049] An environmentally friendly asphalt material, the mass ratio of which includes:

[0050] 30 parts of ceramsite, 18 parts of mineral material, 8 parts of asphalt, 25 parts of red mud, and 0.8 parts of surfactant.

[0051] The ceramsite adopts modified porous ceramsite, and the porous ceramsite adopts silica porous ceramsite, and the preparation method of the silica porous ceramsite comprises the following steps: a1, adding ethyl cellulose to ether and stirring evenly to form a dissolving solution, then adding trichlorophenylsilane and rapidly stirring for 25 minutes to obtain a homogeneous dissolving solution, the concentration of the ethyl cellulose in the ether is 150g / L, the stirring speed is 150r / min, the amount of the trichlorophenylsilane added is 180% of the mass of the ethyl cellulose, and the stirring speed of the rapid stirring is 800r / min; a2, adding fly ash, bentonite, sludge and kaolin into a grinder for grinding treatment to obtain a mixed powder, the mass ratio of the fly ash, bentonite, sludge and kaolin is 35:8:10:1, and the grinding pressure of the grinding treatment is 3MPa; a3, adding the mixed powder into Ultrasonic dispersion is performed in the dissolving solution for 3 hours to obtain a mixed slurry, wherein the concentration of the mixed powder in the dissolving solution is 3000 g / L, the ultrasonic frequency of the ultrasonic treatment is 70 kHz, and the temperature is 8°C; a4, after filtering the mixed slurry, it is placed in a reactor and allowed to stand for 3 hours, then the reactor is stirred and purged for 2 hours to obtain a mixture, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1, the standing temperature is 8°C, the stirring speed of the stirred reactor is 700 r / min, purging uses 38°C nitrogen, and the purging speed is 8 mL / min; a5, granulating the mixture to form solid particles, and sintering at a constant temperature for 2 hours, then placing it in a muffle furnace and sintering it for 25 minutes, washing it, and standing it to dry to obtain ceramsite; the constant temperature sintering temperature is 170°C; the sintering temperature of the muffle furnace is 1100°C.

[0052] Furthermore, the preparation method of the modified porous ceramsite includes the following steps: b1, placing the porous ceramsite in distilled water for ultrasonic treatment for 40 minutes, and drying at a constant temperature to obtain clean porous ceramsite, wherein the mass ratio of the porous ceramsite to distilled water is 1:8, the ultrasonic frequency of the ultrasonic treatment is 70kHz, and the temperature is 40°C; the temperature of the constant temperature drying is 115°C; b2, adding titanium tetrachloride to ethanol to form a dissolving solution, spraying it into a reactor to form a steam atmosphere, and placing the clean porous ceramic in it, standing it for 25 minutes, and then cooling it to 95°C to obtain a coated porous ceramsite, wherein the concentration of titanium tetrachloride in ethanol is 90g / L, and the spraying temperature is 145 ℃, the porous ceramic is placed in the middle section of the reactor, and the standing temperature is 145℃; b3, the coated porous ceramsite is allowed to stand in the reactor for 2h to obtain a preliminary hydrolyzed porous ceramic, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1, and the standing temperature is 8℃; b4, ethyl silicate is added to ether and stirred evenly to form a silicon ether liquid, and then the silicon ether liquid is sprayed onto the surface of the preliminary hydrolyzed porous ceramic, and the surface is allowed to stand at a constant temperature to obtain a surface coated porous ceramic; the concentration of ethyl silicate in ether is 60g / L, the stirring speed is 500r / min, and the spraying speed is 0.2mL / cm 2 , the constant temperature standing temperature is 45°C; b5, the surface coated porous ceramsite is stood in the reactor for 25 minutes, and the modified porous ceramsite is obtained after sintering treatment. The atmosphere in the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 11:1, and the standing temperature is 35°C; the temperature of the sintering treatment is 140°C.

[0053] The mineral material is composed of coarse aggregate, fine aggregate and mineral powder, and the mass ratio of coarse aggregate, fine aggregate and mineral powder is 5:3:1, the coarse aggregate is 8-10mm basalt, and the fine aggregate is limestone less than 2.5mm; the mineral material is pre-treated before use, and the pre-treatment steps include: b1, putting the coarse aggregate and the fine aggregate into ethanol for ultrasonic treatment for 15min, filtering and drying to obtain a preliminary mixed aggregate, the raw material concentration of the ultrasonic treatment is 150g / L, the ultrasonic frequency is 70kHz, the temperature is 30℃, and the drying temperature is 90℃; b2, adding ethyl silicate to ether and stirring evenly to form a dissolved solution, and then putting the preliminary mixed aggregate into and ultrasonically treating it for 40min; obtaining a suspended slurry, the concentration of ethyl silicate in ether is 150g / L, the stirring speed for stirring evenly is 400r / min, the concentration of the preliminary mixed aggregate in the dissolved solution is 400g / L, the frequency of ultrasonic treatment is 70kHz, and the temperature is 12℃;

[0054] b3, adding mineral powder to the suspension and ultrasonically dispersing it for 25 minutes, then drying it, and blowing it into the reactor at a constant temperature to obtain the pre-treated mineral material through deposition, the temperature of the ultrasonic dispersion is 15°C, the ultrasonic frequency is 80kHz, the temperature of the drying is 50°C; the temperature of the constant temperature blowing is 75°C, the blowing rate is 5g / min, the atmosphere of the reactor is a mixed atmosphere of water vapor and nitrogen in a volume ratio of 1:9, and the temperature of the deposition is 120°C.

[0055] The asphalt adopts national standard No. 70 asphalt.

[0056] The surfactant is dodecyltrimethylammonium chloride.

[0057] The method for preparing the environmentally friendly asphalt material comprises the following steps:

[0058] Step 1, stirring ceramsite, mineral material and red mud at high speed to form a mixture; the speed of high-speed stirring is 600r / min;

[0059] Step 2, stirring and heating the asphalt to 170° C. at a stirring speed of 300 r / min to obtain preheated asphalt;

[0060] Step 3, adding a surfactant to the mixture and stirring, and then adding preheated asphalt to obtain an environmentally friendly asphalt material, the stirring speed is 400r / min.

[0061] According to the "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" and "Testing Procedures for Asphalt and Asphalt Mixtures", the mixtures of Examples 1-3 were tested, and the test results are as follows:

[0062]

[0063] Taking the asphalt materials of Examples 1-3 and the comparative example as test samples, according to the GB / T 23761-2020-Formaldehyde test, Examples 1-3 all have good photocatalytic degradation performance, and the degradation rate is not less than 95%, and the comparative example does not show photocatalytic degradation performance. The above test shows that the asphalt materials provided by Examples 1-3 can achieve a good exhaust gas degradation treatment effect.

[0064] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. An environmentally friendly asphalt material, characterized by: The raw materials of the asphalt material include: 20-40 parts of ceramsite, 15-20 parts of mineral material, 3-10 parts of asphalt, 20-30 parts of red mud, and 0.5-1 part of surfactant. The ceramsite is modified porous ceramsite. The preparation method of the modified porous ceramsite comprises the following steps: Step 1, adding ethyl cellulose to diethyl ether and stirring evenly, then adding trichlorophenylsilane and stirring rapidly to obtain a homogeneous solution, wherein the concentration of the ethyl cellulose in the diethyl ether is 100-200 g / L, and the amount of the trichlorophenylsilane added is 150-200% of the mass of the ethyl cellulose; Step 2, adding fly ash, bentonite, sludge and kaolin into a grinder for grinding to obtain a mixed powder, wherein the mass ratio of the fly ash, bentonite, sludge and kaolin is 30-40:5-10:5-15:1; Step 3, adding the mixed powder to the dissolving solution and ultrasonically dispersing to obtain a mixed slurry, wherein the concentration of the mixed powder in the dissolving solution is 1000-4000 g / L; Step 4, after filtering the mixed slurry, putting it into a reactor and standing for 2-4 hours, then stirring and purging for 1-2 hours to obtain a mixture, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, the standing temperature is 5-10°C, and the purging adopts nitrogen at 35-40°C, and the purging speed is 5-10mL / min; Step 5, granulating the mixture into solid particles, sintering at a constant temperature for 1-2 hours, and then sintering in a muffle furnace for 20-30 minutes, washing and standing to dry to obtain porous ceramsite; the temperature of the constant temperature sintering is 150-180° C.; the temperature of the sintering in the muffle furnace is 1000-1100° C.; Step 6, placing the porous ceramsite in distilled water for ultrasonic treatment, and drying at a constant temperature to obtain clean porous ceramsite; Step 7, adding titanium tetrachloride to ethanol to form a dissolving solution, spraying it into a reactor to form a steam atmosphere, and placing clean porous ceramsite in it, standing for 20-30 minutes, and cooling to 90-100° C. to obtain coated porous ceramsite, wherein the concentration of titanium tetrachloride in ethanol is 80-100 g / L, the spraying temperature is 140-150° C., the porous ceramsite is placed in the middle section of the reactor, and the standing temperature is 140-150° C.; Step 8, placing the coated porous ceramsite in a reactor for 1-2 hours to obtain preliminary hydrolyzed porous ceramsite, wherein the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, and the standing temperature is 5-10°C; Step 9, adding ethyl silicate to ether and stirring evenly to form a silicon ether liquid, then spraying the silicon ether liquid onto the surface of the preliminarily hydrolyzed porous ceramsite, and standing at a constant temperature to obtain a surface-coated porous ceramic ceramsite; the concentration of the ethyl silicate in the ether is 50-70 g / L, and the temperature of the constant temperature standing is 40-50° C.; Step 10, the surface coated porous ceramic ceramsite is allowed to stand in a reactor for 20-30 minutes, and the modified porous ceramsite is obtained after sintering treatment. The atmosphere in the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10-12:1, and the standing temperature is 30-40°C; the temperature of the sintering treatment is 120-150°C.

2. The environmentally friendly asphalt material according to claim 1, characterized in that: The mineral material consists of coarse aggregate, fine aggregate and mineral powder, and the mass ratio of the coarse aggregate, fine aggregate and mineral powder is 4-5:3:1-2.

3. The environmentally friendly asphalt material according to claim 2, characterized in that: The coarse aggregate is 8-10 mm basalt, and the fine aggregate is limestone less than 2.5 mm.

4. The environmentally friendly asphalt material according to claim 2, characterized in that: The mineral material is pre-treated before use, and the pre-treatment steps include: Step 1, placing the coarse aggregate and the fine aggregate in ethanol for ultrasonic treatment, filtering and drying to obtain a preliminary mixed aggregate; Step 2, adding ethyl silicate to ether and stirring evenly to obtain a dissolving solution, then adding the preliminary mixed aggregate and ultrasonically treating to obtain a suspended slurry, wherein the concentration of the ethyl silicate in the ether is 100-200 g / L, and the concentration of the preliminary mixed aggregate in the dissolving solution is 200-500 g / L; Step 3, adding the mineral powder to the suspended slurry for ultrasonic dispersion, then drying, and blowing it into the reactor at a constant temperature to obtain the pre-treated mineral material through deposition. The temperature of the constant temperature blowing is 70-80°C, the blowing speed is 3-6g / min, the atmosphere of the reactor is a mixed atmosphere of water vapor and nitrogen in a volume ratio of 1:9, and the deposition temperature is 100-140°C.

5. The environmentally friendly asphalt material according to claim 1, characterized in that: The asphalt adopts one or both of national standard No. 70 asphalt and No. 90 asphalt.

6. The environmentally friendly asphalt material according to claim 1, characterized in that: The surfactant is dodecyltrimethylammonium chloride.

7. The environmentally friendly asphalt material according to claim 1, characterized in that: The preparation method of the environmentally friendly asphalt material comprises the following steps: Step 1, stirring ceramsite, mineral material and red mud at high speed to form a mixture; the speed of high-speed stirring is 500-700r / min; Step 2, stirring and heating the asphalt to 160-180° C. at a stirring speed of 200-400 r / min to obtain preheated asphalt; Step 3, adding a surfactant to the mixture and stirring, and then adding preheated asphalt to obtain an environmentally friendly asphalt material, wherein the stirring speed is 300-500 r / min.

Citation Information

Patent Citations

  • Specific modified cold-mixed asphalt for heat-area normal-temperature blending asphalt concrete

    CN101735626A

  • Asphalt mixture taking red mud as filler and preparation method thereof

    CN105753375A

  • Bituminous mixture with physically modified red mud replacing mineral powder and preparation method of bituminous mixture

    CN109503032A

  • Preparation process of ceramsite asphalt pavement material

    CN112551948A

  • Asphalt modified with red mud for porous pavement material and application thereof

    US11370707B1